2017
DOI: 10.3389/fcimb.2017.00372
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica EhCP112 Dislocates and Degrades Claudin-1 and Claudin-2 at Tight Junctions of the Intestinal Epithelium

Abstract: During intestinal invasion, Entamoeba histolytica opens tight junctions (TJs) reflected by transepithelial electrical resistance (TEER) dropping. To explore the molecular mechanisms underlying this, we studied in vitro and in vivo the damage produced by the recombinant E. histolytica cysteine protease (rEhCP112) on TJ functions and proteins. rEhCP112 reduced TEER in Caco-2 cells in a dose- and time-dependent manner; and EhCP112-overexpressing trophozoites provoked major epithelial injury compared to control tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 60 publications
0
44
0
Order By: Relevance
“…All these processes are performed with the active participation of lipids (Espinosa-Cantellano and Martinez-Palomo, 2000;Byekova et al, 2010;Das and Nozaki, 2018). Trophozoites degrade the mucus layer by the secretion of glycosidases and cysteine proteases (Espinosa-Cantellano and Martinez-Palomo, 2000;Cuellar et al, 2017). Thanks its lipid composition, amebic membranes are resistant to the lytic compounds of the parasite (Andrä et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these processes are performed with the active participation of lipids (Espinosa-Cantellano and Martinez-Palomo, 2000;Byekova et al, 2010;Das and Nozaki, 2018). Trophozoites degrade the mucus layer by the secretion of glycosidases and cysteine proteases (Espinosa-Cantellano and Martinez-Palomo, 2000;Cuellar et al, 2017). Thanks its lipid composition, amebic membranes are resistant to the lytic compounds of the parasite (Andrä et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The EhCPADH complex, formed by a cysteine protease (EhCP112) and an adhesin (EhADH), is also involved in adherence to and destruction of the epithelium (Cuellar et al, 2017;Hernández-Nava et al, 2017). Through the cysteine protease, this complex destroys the mucus layer; and by the adhesin, it enhances the trophozoites adherence to the epithelium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the trophozoites and their CM produced a substantial cytopathic effect and an important decrease of TEER in the RBMEC culture. Previous reports showed that the cytopathic damage produced by A. castellanii, E. histolytica, Toxoplasma gondii, and Giardia duodenalis in HBMEC and MDCK cells, was the result of the action of their proteases (Betanzos et al 2013;Briceno et al 2016;Cuellar et al 2017;Halliez et al 2016;Khan and Siddiqui 2009;Shibayama et al 2013). To evaluate the damage produced by the amoebic proteases, we preincubated the trophozoites and their CM with E-64 or Aprotinin and observed that the cysteine proteases inhibitor but not the serine proteases exerted a protective effect on the endothelial monolayer.…”
Section: Discussionmentioning
confidence: 96%
“…EhCPADH, EhADH, and EhCP112 are secreted during trophozoite attack (Ocádiz et al, 2005 ; Bolaños et al, 2016 ). Moreover, an EhCP112 recombinant protein drops TEER of epithelial cells, and dislocates and degrades junctional molecules, including claudin-1, claudin-2, β-catenin, E-cadherin, desmoplakin-I/II and desmoglein-2 (Cuellar et al, 2017 ; Hernández-Nava et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%